Smart Stick Revolutionizes Mobility for the Visually Impaired: Tongkat Pintar Merevolusi Mobilitas bagi Tunanetra - Alfian, Moh.; Ayuni, Shazana Dhiya (Indonesian Journal of Innovation Studies, 2024)
Visual impairment significantly hinders daily activities, necessitating innovative solutions. This study develops and tests a smart walking stick using NodeMCU ESP-8266, HCSR-04 ultrasonic sensor, DFPlayer, and GPS, monitored via the Blynk app. Employing a research and development approach, the device demonstrated 100% accuracy in obstacle detection and location tracking, providing real-time feedback through audio notifications and smartphone monitoring. This smart walking stick enhances mobility and safety for visually impaired users, representing a significant advancement in assistive technology. Highlights: Accurate Obstacle Detection: 100% accuracy with HCSR-04 ultrasonic sensor. Real-time Monitoring: GPS tracking via Blynk app. Enhanced Mobility: Increases safety and independence for visually impaired users. Keywords: Visual impairment, Smart walking stick, Ultrasonic sensor, GPS tracking, IoT